SLC16 Family: From Atomic Structure to Human Disease. Issue 1 (January 2021) - Bosshart, Patrick D.; Charles, Roch-Philippe; Garibsingh, Rachel-Ann A.; Schlessinger, Avner; Fotiadis, Dimitrios
Abstract : The solute carrier 16 (SLC16) family represents a diverse group of membrane proteins mediating the transport of monocarboxylates across biological membranes. Family members show a variety of functional roles ranging from nutrient transport and intracellular pH regulation to thyroid hormone homeostasis. Changes in the expression levels and transport function of certain SLC16 transporters are manifested in severe health disorders including cancer, diabetes, and neurological disorders. L-Lactate-transporting SLC16 family members play essential roles in the metabolism of certain tumors and became validated drug targets. This review illuminates the SLC16 family under a new light using structural information obtained from a SLC16 homolog. Furthermore, the role of these transporters in cancer metabolism and how their inhibition can contribute to anticancer therapy are discussed. Highlights: The solute carrier 16 (SLC16) family is a diverse group of monocarboxylate transporters (MCTs). This is reflected in the diversity of transported substrates (e.g., L-lactate, pyruvate, ketone bodies, drugs, metabolites, aromatic amino acids, hormones). Changes in the functionality and loss of function of certain family members are associated with severe health disorders (e.g., cancer, diabetes, neurological disorders, eye diseases). The substrate-bound X-ray structure of the L-lactate-transporting SfMCT represents the first structural information on the SLC16 family and provides insights into the molecular working mechanism of L-lactate-transporting family members. The pharmacologically relevant outward-open conformation of the SfMCT structure can be used as a template for homology modelling of human MCTs. The L-lactate-transporting MCT1 and 4 are important in the metabolism of certain tumors and represent validated drug targets.